2021
DOI: 10.1653/024.104.0307
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Soybean Looper (Lepidoptera: Noctuidae) in the Southeastern USA and Implications for Pheromone-Based Research and Management

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Cross-attraction of artificial lures is frequently reported among moth species that share pheromone components. 43 For instance, Wakamura et al found that the sex pheromone of S. frugiperda in Japan, Z9-14:OAc and Z7-12:OAc ratio between 100:1 and 100:10, also attracted other noctuid moths, such as Mythimna loreyi and Chrysodeixis eriosoma. 44 Similar cross-attraction happened in field experiments trapping A. lepigone 33 and Chrysodeixis includens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-attraction of artificial lures is frequently reported among moth species that share pheromone components. 43 For instance, Wakamura et al found that the sex pheromone of S. frugiperda in Japan, Z9-14:OAc and Z7-12:OAc ratio between 100:1 and 100:10, also attracted other noctuid moths, such as Mythimna loreyi and Chrysodeixis eriosoma. 44 Similar cross-attraction happened in field experiments trapping A. lepigone 33 and Chrysodeixis includens.…”
Section: Discussionmentioning
confidence: 99%
“…44 Similar cross-attraction happened in field experiments trapping A. lepigone 33 and Chrysodeixis includens. 43 During our field experiments 1 and 2, a few non-target male moths were captured besides M. crassisigna. Lures loaded with only Z7-12:OAc showed strong attractiveness to Ct. albostriata, whose sex pheromone is identified as Z7-12:OAc and Z5-10:OAc (2:1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of pheromones is advantageous in agriculture as easy monitoring pest, lower cost, host specificity and easy to use [32]. US EPA has registered 30 product based on mating disruption pheromones as biological agents against lepidopteron pest [33].…”
Section: Pheromonesmentioning
confidence: 99%
“…includens damages various crops, particularly soybean and cotton, and reduces their yields (Herzog, 1980;Musser et al, 2022). It overwinters and reproduces primarily in the regions of Central and South Americas, the Caribbean, and annually migrates northward, reaching peak populations in August to September in the southern United States (Carner et al, 1974;Fleming et al, 2021;Mitchell et al, 1975;Shaw et al, 2021). Soybean looper resistance has been reported for various classes of synthetic insecticides, including organophosphates, carbamates, pyrethroids, and chitin synthesis inhibitors (Felland et al, 1990;Mascarenhas & Boethel, 1997;Mink et al, 1993;Perini et al, 2021;Stacke et al, 2019Stacke et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%